1990
DOI: 10.1063/1.859556
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on vortex dynamics in pure electron plasmas

Abstract: Magnetically confined columns of electrons are excellent experimental manifestations of two-dimensional (2-D) vortices in an inviscid fluid. Surface charge perturbations on the electron column (diocotron modes) are equivalent to surface ripples on extended vortices; and unstable diocotron modes on hollow electron columns are examples of the Kelvin–Helmholtz instability. Experiments demonstrate that the stable and unstable modes are distinct and may coexist, having different frequencies and radial eigenfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
172
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(176 citation statements)
references
References 22 publications
4
172
0
Order By: Relevance
“…Perturbed vortices such as ͑1͒ can be realized experimentally by manipulating columns of magnetically confined electron plasmas. 4 Once the external perturbation is switched off or is reduced to a low level, Eq. ͑1͒ defines a disturbed smooth vortex, and self-induction then leads to a nonelliptical rearrangement of the vorticity.…”
mentioning
confidence: 99%
“…Perturbed vortices such as ͑1͒ can be realized experimentally by manipulating columns of magnetically confined electron plasmas. 4 Once the external perturbation is switched off or is reduced to a low level, Eq. ͑1͒ defines a disturbed smooth vortex, and self-induction then leads to a nonelliptical rearrangement of the vorticity.…”
mentioning
confidence: 99%
“…Some recent experimental work using nonneutral plasmas as a laboratory analogue of inviscid two-dimensional fluid mechanics (Driscoll & Fine 1990) may be relevant. Experiments with this system (Pillai & Gould 1994) have shown that stable disturbances have an initial exponential decay which is then followed by a protracted algebraic decay.…”
Section: To Summarizementioning
confidence: 99%
“…In the Euler case, the vorticity plays the role of the density n, and the stream function plays the role of the electrostatic potential φ. This isomorphism has been highlighted in a different context [18,19]. A major difference is that in [18,19], the plasma is surrounded by a cylindrical conductor, whereas in our model Poisson's equation is solved with free space boundary conditions.…”
mentioning
confidence: 99%
“…This isomorphism has been highlighted in a different context [18,19]. A major difference is that in [18,19], the plasma is surrounded by a cylindrical conductor, whereas in our model Poisson's equation is solved with free space boundary conditions. Some of the phenomena we discuss in this letter occur in elongated beams that would be hard to create in the experiments described in [18,19] and have not been studied in that context.…”
mentioning
confidence: 99%
See 1 more Smart Citation